Developing as Teacher Leaders for Social Justice: The Influence of a Teacher-Leadership Graduate Program. Issue 4 (2nd October 2018) - Jacobs, Jennifer; Crowell, Lyn
Abstract: This qualitative study used focus groups to examine teacher leaders' perceptions of how they developed as a result of being in a teacher-leadership graduate program with a focus on social justice. Findings point to the teacher leaders' development of a social-justice lens and a leadership lens to frame their work inside and outside of the classroom. The development of a social-justice lens promoted teacher leaders' critical consciousness about their identity and practices in their classrooms. The combination of a social justice and leadership lens promoted teacher leaders' critique of the practices and policies within the school and district. In addition, teacher leaders engaged in action or praxis in relation to social-justice issues within their schools. Implications for teacher-leadership programs include the need for a key focus on critical self- reflection, action research, and including practical and conceptual tools within the curriculum.